Metal–Organic Framework‐Based Stimuli‐Responsive Systems for Drug Delivery. Issue 1 (20th November 2018) - Cai, Wen; Wang, Junqing; Chu, Chengchao; Chen, Wei; Wu, Chunsheng; Liu, Gang
Abstract: With the rapid development of nanotechnology, stimuli‐responsive nanomaterials have provided an alternative for designing controllable drug delivery systems due to their spatiotemporally controllable properties. As a new type of porous material, metal–organic frameworks (MOFs) have been widely used in biomedical applications, especially drug delivery systems, owing to their tunable pore size, high surface area and pore volume, and easy surface modification. Here, recent progress in MOF‐based stimuli‐responsive systems is presented, including pH‐, magnetic‐, ion‐, temperature‐, pressure‐, light‐, humidity‐, redox‐, and multiple stimuli‐responsive systems for the delivery of anticancer drugs. The remaining challenges and suggestions for future directions for the rational design of MOF‐based nanomedicines are also discussed. Abstract : Reaching the advanced drug delivery potential of metal–organic frameworks (MOFs) featuring spatiotemporally controllable properties is of utmost importance. MOFs have the advantages of high drug loading capacities, easy functionalization, and good biocompatibility. The development of MOF‐based stimuli‐responsive drug delivery systems provides a means of designing exciting nanoformulations for clinical translation in future nanomedicines.